Polyester material for biodegradable heat shrink film and product thereof
By polymerizing 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzyl alcohol and biodegradable monomers, a new biobased polyester material was prepared, which solved the problem of difficulty in degradation and insufficient performance of PETG heat shrink film materials after use, and achieved efficient degradation and performance improvement of heat shrink films.
Patent Information
- Application Number
- CN202510258230.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing PETG heat shrink film materials are difficult to degrade after use, and their stability and structural density are low, which affects their aging resistance, gas barrier properties and mechanical strength.
A new biobased polyester material was prepared by polymerizing 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzene dimethanol and biodegradable monomers, and the degradability and mechanical properties of the material were improved by optimizing the polymerization process.
The degradability, aging resistance, gas barrier ability and mechanical strength of the heat shrink film are significantly improved, meeting the needs of environmental protection and performance improvement.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer synthesis and processing, and in particular to a polyester material for a biodegradable heat shrinkable film and a product thereof. Background Art
[0002] Heat shrink film is a label material used for the outside of containers, usually used for packaging of plastic bottles, glass bottles and other containers. This film material has excellent gloss, good fit and shrinkage, so it can be tightly wrapped on the surface of the container to form a complete and exquisite packaging effect. Its glossiness and shrinkage make the packaging pattern on the container more vivid and visually impactful, which can effectively enhance the shelf appeal of the product, create a unique container effect, and attract consumers' attention. Therefore, heat shrink film is widely used in the outer packaging of various products, especially in the fields of food, beverages, cosmetics and daily consumer goods. It plays an important role.
[0003] At present, common materials for heat shrink films include polyvinyl chloride (PVC), polyethylene terephthalate glycol (PETG) and oriented polystyrene (OPS). Among them, PETG has become the mainstream material in the field of heat shrink films due to its high shrinkage rate, excellent transparency, non-toxicity and tastelessness, and good mechanical properties. PETG film not only has excellent visual effects, but also has a low self-shrinkage rate. Therefore, it is more stable during the packaging process, has a longer storage period, is not easy to deform, and meets environmental protection requirements.
[0004] However, there are also problems with PETG heat shrink film that cannot be ignored. Although it has many advantages, the main component of PETG is a non-biodegradable material based on petrochemical raw materials, so it is difficult to degrade naturally after use, and it is also very difficult to recycle. This means that the heat shrink film may exist in the environment for a long time after use, especially when the waste is not effectively treated, which will cause pollution to the ecological environment. In addition, with the increasing global attention to sustainable development and environmental protection issues, the voices demanding more environmentally friendly materials are getting louder and louder. Under the "dual carbon" goal, many countries and regions are accelerating the research and application of biodegradable materials, recyclable materials and green packaging technologies, hoping to reduce dependence on non-renewable resources and promote the realization of a circular economy. Therefore, more and more bio-based materials are beginning to attract attention as an alternative to heat shrink film.
[0005] 2,5-Furandicarboxylic acid (FDCA) is a green and renewable chemical intermediate first synthesized by Fettig and Heintzelmann in 1876. It has strong chemical stability, can be dissolved in water under alkaline conditions, and appears as a white solid powder in an acidic environment. 2,5-Furandicarboxylic acid is a very important raw material in the chemical industry, especially in the synthesis of corrosion-resistant plastics. At the same time, it is also an important component of bio-based industrial products and is listed as one of the biorefined carbohydrate derivatives. Due to its unique properties, 2,5-Furandicarboxylic acid is widely used in the production of green and biodegradable polyester materials, especially in replacing traditional terephthalic acid (PTA).
[0006] In the production process of polyester, 2,5-furandicarboxylic acid can effectively replace traditional terephthalic acid and become a green and renewable polyester monomer. The polyester material synthesized based on 2,5-furandicarboxylic acid has excellent barrier properties, heat resistance and mechanical strength, and can significantly improve the overall performance of heat shrink film. Especially in terms of environmental protection, the polyester material based on 2,5-furandicarboxylic acid has better biodegradability, which meets the demand of today's society for environmentally friendly packaging materials.
[0007] However, although 2,5-furandicarboxylic acid and its polyester materials have good performance in theory, the existing technology still has some limitations. The polyester obtained by the polymerization of 2,5-furandicarboxylic acid and diols still contains a certain proportion of non-degradable components, which to a certain extent affects the complete degradability of the heat shrink film. In addition, the stability and structural density of existing polyester materials are relatively low, resulting in the performance of the obtained heat shrink film in terms of aging resistance, gas barrier properties and mechanical strength. Therefore, it is urgent to develop a new type of bio-based polyester material to further improve the degradability, aging resistance, gas barrier properties and mechanical strength of the heat shrink film.
[0008] In summary, with the increase in environmental protection needs and the development of technology, bio-based polyester based on 2,5-furandicarboxylic acid has become an ideal alternative material, which can provide better performance for heat shrink film and meet the environmental protection requirements of degradability and recyclability. Future research should focus on optimizing the polymerization process, reducing non-degradable components, and further improving the comprehensive performance of polyester materials, thereby promoting the popularization and application of sustainable packaging materials. Summary of the invention
[0009] In view of the defects of the prior art, the object of the present invention is to provide a bio-based polyester material of 2,5-furandicarboxylic acid for biodegradable heat shrinkable film and its product which can further improve the degradability of the heat shrinkable film and has excellent aging resistance, gas barrier capacity and mechanical strength.
[0010] The present invention provides a polyester material for a biodegradable heat shrinkable film, wherein the polyester material is prepared by polymerizing 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and a biodegradable monomer; The biodegradable monomer is prepared by the following steps: adding dimethyl itaconate, ethylene oxide and concentrated sulfuric acid into a reactor, heating to 70-75° C. for reflux reaction for 1-3 hours, cooling, standing and separating to obtain the biodegradable monomer.
[0011] The present invention uses biodegradable monomers as main diol monomers for polymerization, and the branched structure of dimethyl ester can shorten the distance between polyester molecules, thereby improving the density and processability of the polyester material, so that the barrier capacity and mechanical strength of the polyester material to gas molecules can be improved. The structure of dimethyl itaconate can be degraded with the structure of 2,5-furandicarboxylic acid under the action of microorganisms, thereby improving the degradability and degradation effect of the polyester. Meanwhile, the raw materials of dimethyl itaconate and 2,5-furandicarboxylic acid are widely available and can be regenerated, thereby further reducing pollution.
[0012] Furthermore, the mass concentration of the concentrated sulfuric acid is 70-98wt%; and the molar ratio of dimethyl itaconate to ethylene oxide is 1:2-3.
[0013] Furthermore, the polyester material for the biodegradable heat shrinkable film is prepared by the following steps: (1) Esterification: Add 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and a biodegradable monomer into a reactor, and carry out an esterification reaction at a temperature of 250-270°C for 2-3 hours. After the reaction is completed, distill off the excess reactants to obtain an esterification product; (2) Polycondensation: The esterification product is subjected to polycondensation at 280-290° C. under a catalyst and in a pressure range of 0.1-10 kPa for a reaction time of 3-5 hours. After the reaction is completed, the polyester material for the biodegradable heat shrinkable film is obtained by cooling, filtering, washing and drying.
[0014] The polyester material for biodegradable heat shrinkable film provided by the present invention can not only make up for the structural defects of each other through the copolymerization of three monomers, but also give full play to the effects of the three monomers in structure and chemical properties, and can also play a synergistic role, so that the prepared polyester material can have excellent aging resistance and biodegradability at the same time without affecting its mechanical properties.
[0015] Furthermore, in the step (1), the mass ratio of 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and the biodegradable monomer is (10-14): (2-3): (6-8).
[0016] In the present invention, 3,6-difluoro-1,2-benzenedimethanol is added as a functional monomer. On the one hand, its fluorine-containing structure can improve the aging effect of the polyester material on ultraviolet, oxidation or acid-base factors, and improve the aging resistance of the obtained heat shrinkable film; on the other hand, it can improve the structural stability of the polyester molecules, thereby improving the tensile strength, elongation at break and other mechanical properties of the obtained heat shrinkable film, and further improve the use value of the heat shrinkable film.
[0017] Furthermore, in step (2), the catalyst is selected from one of n-butyl titanate and tetraisopropyl titanate.
[0018] A heat shrinkable film of a polyester material comprising any one of the above biodegradable heat shrinkable films, wherein the heat shrinkable film is a three-layer composite structure, including a surface film layer and a core film layer sandwiched between two surface film layers; The total thickness of the heat shrinkable film is 20-50 μm; the thickness of the surface film layer is 2-5 μm; by weight, The surface film layer material comprises 85-95 parts of a polyester material of a biodegradable heat shrinkable film, 3-5 parts of a plastic degradation masterbatch and 2-6 parts of an opening agent; The core film layer material comprises 75-90 parts of a polyester material of a biodegradable heat shrinkable film, 5-10 parts of a white masterbatch and 3-5 parts of a plastic degradation masterbatch.
[0019] The polyester material of the biodegradable heat shrinkable film of the present invention has excellent mechanical strength and biodegradability, and can reduce the amount of plastic degradation masterbatch and white masterbatch added to the heat shrinkable film, thereby improving recyclability.
[0020] Furthermore, the opening agent is silicon dioxide; the white masterbatch is titanium dioxide; and the plastic degradation masterbatch is polylactic acid.
[0021] Furthermore, the heat shrinkable film is prepared by the following steps: through a three-layer co-extrusion biaxial stretching production process, the core film layer material and the surface film layer material are respectively fed, mixed, melt-plasticized and filtered and extruded, and then the heat shrinkable film is obtained after cast film, longitudinal stretching, transverse stretching, trimming and winding.
[0022] Furthermore, the filtration extrusion temperature of the core film layer is 250°C-270°C, and the filtration extrusion temperature of the surface film layer is 255°C-275°C; The preheating temperature in the longitudinal stretching is 95-105°C, the longitudinal stretching temperature is 85°C-95°C, the longitudinal stretching ratio is 1.0-3.0, the longitudinal stretching setting temperature is 75°C-90°C, and the longitudinal stretching setting time is 3-6 seconds; The preheating temperature in the transverse stretching is 105-125° C., the transverse stretching temperature is 85° C.-100° C., the transverse stretching ratio is 4-5.5 times, the transverse stretching setting temperature is 75° C.-90° C., and the transverse stretching setting time is 5-10 seconds.
[0023] Beneficial effects: (1) The polyester material for biodegradable heat shrinkable film and the degradable heat shrinkable film containing the same provided by the present invention are prepared by using 2,5-furandicarboxylic acid instead of terephthalic acid and polymerizing 3,6-difluoro-1,2-benzenedimethanol and a biodegradable monomer as an alcohol monomer. The prepared polyester material has excellent degradability, stability and bonding density, thereby significantly improving the degradability, aging resistance, gas barrier ability and mechanical strength of the prepared heat shrinkable film.
[0024] (2) The present invention can further increase the content of degradable components in polyester and improve the degradation rate of polyester by preparing biodegradable monomers to replace conventional non-biodegradable diol monomers.
[0025] (3) In the polyester material for biodegradable heat shrinkable film provided by the present invention, by polymerizing the biodegradable monomer as the main diol monomer, the branched structure of the dimethyl ester can increase the density of the polyester material, thereby improving the barrier ability to gas molecules and the mechanical strength of the polyester.
[0026] (4) In the polyester material for biodegradable heat shrinkable film provided by the present invention, 3,6-difluoro-1,2-benzenedimethanol is added as a functional monomer. On the one hand, its fluorine-containing structure and benzene ring structure can improve the aging effects of the polyester material on ultraviolet, oxidation or acid-base factors, thereby improving the aging resistance of the heat shrinkable film; on the other hand, it can improve the structural stability of the polyester molecules, thereby improving the tensile strength, elongation at break and other mechanical properties of the heat shrinkable film, thereby further improving the use value of the heat shrinkable film.
[0027] (5) The polyester material for the biodegradable heat shrinkable film provided by the present invention is copolymerized by three monomers, thereby synergistically enhancing the aging resistance and biodegradability of the polyester material without affecting its mechanical properties.
[0028] (6) The biodegradable heat shrinkable film provided by the present invention, which contains the polyester material for the biodegradable heat shrinkable film, has a plastic degradation masterbatch added to the material, which can cause it to quickly disintegrate under the action of microorganisms, thereby improving the degradation efficiency of the polyester material; in terms of structure, the polyester material of the biodegradable heat shrinkable film is used as the main material, which can significantly improve the overall degradability, aging resistance, gas barrier capacity and mechanical strength of the heat shrinkable film, thereby expanding the application range of the heat shrinkable film and reducing the recycling cost. DETAILED DESCRIPTION
[0029] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0030] PETG is a high-transparency PETG raw material purchased from Shenzhen Dilingwei Technology Co., Ltd.; the remaining reagents and equipment are conventional reagents and equipment in this technical field.
[0031] Preparation of biodegradable monomers The biodegradable monomer is prepared by the following steps: in a reactor, 1 mol of dimethyl itaconate, 2 mol of ethylene oxide and 0.1 mL of concentrated sulfuric acid with a mass concentration of 95 wt% are added, the temperature is raised to 50° C. and refluxed for reaction for 3 hours, and the biodegradable monomer is obtained after cooling, standing and separating the oil layer.
[0032] Polyester material-1 preparation The polyester material for the biodegradable heat shrinkable film is prepared according to the following steps, in parts by weight: 1. Esterification: Add 10 parts of 2,5-furandicarboxylic acid, 2.5 parts of 3,6-difluoro-1,2-benzenedimethanol and 8 parts of biodegradable monomers into a reactor, and carry out esterification reaction at a temperature of 270°C for 3 hours. After the reaction is completed, distill off the excess reactants to obtain the esterification product; 2. Polycondensation: The esterification product was polycondensed at 285°C and a pressure of 5 kPa using n-butyl titanate as a catalyst for 4 hours. After the reaction, the polyester material 1 was obtained by cooling, filtering, washing and drying.
[0033] Polyester material-2 preparation The preparation is basically the same as that of polyester material-1, except that 3,6-difluoro-1,2-benzenedimethanol and the biodegradable monomer are respectively replaced with equal amounts of ethylene glycol.
[0034] Polyester material-3 preparation The preparation is basically the same as that of polyester material-1, except that the biodegradable monomer is replaced by an equal amount of hexylene glycol.
[0035] Polyester material-4 preparation The preparation is basically the same as polyester material-1, except that 3,6-difluoro-1,2-benzenedimethanol is replaced with an equal amount of ethylene glycol.
[0036] Example 1 Preparation of a biodegradable heat shrinkable film containing polyester material for a biodegradable heat shrinkable film: Through a three-layer co-extrusion biaxial stretching production process, the core film layer material and the surface film layer material are respectively fed, mixed, melt-plasticized and filtered and extruded, and then the heat shrinkable film is obtained after film casting, longitudinal stretching, transverse stretching, trimming and winding; by weight, the surface film layer material includes 95 parts of polyester material-1, 3 parts of polylactic acid and 2 parts of silicon dioxide; the core film layer material includes 85 parts of polyester material-1, 10 parts of titanium dioxide and 5 parts of polylactic acid; The filtration extrusion temperature of the core membrane layer is 260°C, and the filtration extrusion temperature of the surface membrane layer is 270°C; The preheating temperature in the longitudinal stretching is 100°C, the longitudinal stretching temperature is 90°C, the longitudinal stretching ratio is 2.5 times, the longitudinal stretching setting temperature is 90°C, and the longitudinal stretching setting time is 5 seconds; the preheating temperature in the transverse stretching is 120°C, the transverse stretching temperature is 90°C, the transverse stretching ratio is 5.0 times, the transverse stretching setting temperature is 90°C, and the transverse stretching setting time is 8 seconds; the obtained heat shrinkable film containing polyester material has a layer thickness of 50μm and a surface film layer thickness of 5μm.
[0037] Example 2 Basically the same as Example 1, except that, by weight, the surface film layer material comprises 90 parts of polyester material-1, 5 parts of polylactic acid and 5 parts of silicon dioxide; In terms of weight, the core film layer material includes 75 parts of polyester material-1, 10 parts of titanium dioxide and 3 parts of polylactic acid.
[0038] Example 3 Basically the same as Example 1, except that, by weight, the surface film layer material comprises 85 parts of polyester material-1, 5 parts of polylactic acid and 5 parts of silicon dioxide; In terms of weight, the core film layer material includes 80 parts of polyester material-1, 7 parts of titanium dioxide and 3 parts of polylactic acid.
[0039] Comparative Example 1 The method is basically the same as Example 1, except that the polyester material-1 in the surface film layer material and the core film layer material is replaced with an equal amount of PETG.
[0040] Comparative Example 2 The method is basically the same as Example 1, except that the polyester material-1 in the surface film layer material and the core film layer material is replaced by an equal amount of polyester material-2.
[0041] Comparative Example 3 The method is basically the same as Example 1, except that the polyester material-1 in the surface film layer material and the core film layer material is replaced by an equal amount of polyester material-3.
[0042] Comparative Example 4 The method is basically the same as Example 1, except that the polyester material-1 in the surface film layer material and the core film layer material is replaced by an equal amount of polyester material-4.
[0043] Performance Testing 1. Biodegradation rate test: According to the method described in Appendix A of standard QB / T 2461-1999 "Degradable Polyethylene Film for Packaging", the aerobic biodegradation rates of the products of Examples 1-3 and Comparative Examples 1-4 were tested for 30 days.
[0044] 2. Heat aging resistance test: The products of Examples 1-3 and Comparative Examples 1-4 were aged in an aging box at 55°C and 60% humidity for 7 days, and then mechanical properties were tested using a universal tensile machine, and the tensile strength without breaking time was recorded -1.
[0045] 3. UV aging resistance test: The products of Examples 1-3 and Comparative Examples 1-4 were tested in an aging box under the condition of UV intensity of 5000 μw / cm 2 The wavelength of the UV lamp is 280-400nm, the aging temperature is 50℃, the aging time is 7 days, and then a universal tensile testing machine is used to test the mechanical properties, and the tensile strength without breakage holding time is recorded -2.
[0046] 4. Gas barrier capability test: According to GB / T 1038-2000 "Plastic film and sheet gas permeability test method", the oxygen barrier properties of the products of Examples 1-3 and Comparative Examples 1-4 were tested.
[0047] 5. Mechanical property testing: According to the testing standard of GB / T 13519-2016, the tensile strength and elongation at break of the products of Examples 1-3 and Comparative Examples 1-4 were tested respectively.
[0048] The test results are shown in the following table: Table 1 Test results of test 1-3 Table 2 Test results of test 4-5 According to the comparison of the test results of Examples 1-3 with those of Comparative Example 1, the degradable heat shrinkable film containing polyester material provided by the present invention has excellent biodegradability compared with the PETG heat shrinkable film in the prior art, and has strong resistance to heat aging and ultraviolet aging, can be widely used in the field of heat shrinkable films for a long time, and reduces the recycling cost.
[0049] According to the comparison of the test results of Examples 1-3 and Comparative Examples 2-4, it can be seen that the degradable heat shrinkable film provided by the present invention uses the polyester material for biodegradable heat shrinkable film as the main material, and the 3,6-difluoro-1,2-benzenedimethanol and biodegradable monomers in its structure can significantly improve the biodegradability and heat aging resistance and ultraviolet aging resistance of the heat shrinkable film, and has a certain synergistic effect, which can further improve the performance of the polyester and the heat shrinkable film.
[0050] According to the comparison of the test results of Examples 1-3 with those of Comparative Example 1, the degradable heat shrinkable film containing the polyester material for the biodegradable heat shrinkable film provided by the present invention has better gas barrier capacity and mechanical properties than the PETG heat shrinkable film in the prior art, and can improve the strength of the heat shrinkable film.
[0051] According to the comparison of the test results of Examples 1-3 and Comparative Examples 2-4, it can be seen that the biodegradable heat shrinkable film provided by the present invention uses the polyester material of the biodegradable heat shrinkable film as the main material, and the 3,6-difluoro-1,2-benzenedimethanol and biodegradable monomers in its structure can further improve the gas barrier ability and mechanical strength of the heat shrinkable film, and has a certain synergistic effect, which can further improve the performance of the polyester and the heat shrinkable film.
[0052] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyester material for a biodegradable heat shrinkable film, characterized in that: The polyester material is prepared by polymerizing 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and a biodegradable monomer; The biodegradable monomer is prepared by the following steps: adding dimethyl itaconate, ethylene oxide and concentrated sulfuric acid into a reactor, heating to 70-75° C. for reflux reaction for 1-3 hours, cooling, standing and separating to obtain the biodegradable monomer.
2. The polyester material for biodegradable heat shrinkable film according to claim 1, characterized in that: The mass concentration of the concentrated sulfuric acid is 70-98wt%; the molar ratio of dimethyl itaconate to ethylene oxide is 1:2-3.
3. The polyester material for biodegradable heat shrinkable film according to claim 1, characterized in that: The polyester material is prepared by the following steps: (1) Esterification: Add 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and a biodegradable monomer into a reactor, and carry out an esterification reaction at a temperature of 250-270°C for 2-3 hours. After the reaction is completed, distill off the excess reactants to obtain an esterification product; (2) Polycondensation: The esterification product is subjected to polycondensation at 280-290° C. under a catalyst and in a pressure range of 0.1-10 kPa for a reaction time of 3-5 hours. After the reaction is completed, the polyester material for the biodegradable heat shrinkable film is obtained by cooling, filtering, washing and drying.
4. The polyester material for biodegradable heat shrinkable film according to claim 3, characterized in that: In the step (1), the mass ratio of 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and the biodegradable monomer is (10-14): (2-3): (6-8).
5. The polyester material for biodegradable heat shrinkable film according to claim 4, characterized in that: In the step (1), the mass ratio of 2,5-furandicarboxylic acid, 3,6-difluoro-1,2-benzenedimethanol and the biodegradable monomer is 10:2.5:
8.
6. The polyester material for biodegradable heat shrinkable film according to claim 3, characterized in that: The catalyst in step (2) is selected from one of n-butyl titanate and tetraisopropyl titanate.
7. A heat shrinkable film comprising the polyester material for biodegradable heat shrinkable film according to any one of claims 1 to 6, characterized in that: The heat shrinkable film is a three-layer composite structure, including a surface film layer and a core film layer sandwiched between two surface film layers; The total thickness of the heat shrinkable film is 20-50 μm; the thickness of the surface film layer is 2-5 μm; The surface film layer material comprises 85-95 parts of a polyester material for a biodegradable heat shrinkable film, 3-5 parts of a plastic degradation masterbatch and 2-6 parts of an opening agent by weight; In terms of weight, the core film layer material comprises 75-90 parts of polyester material for biodegradable heat shrinkable film, 5-10 parts of white masterbatch and 3-5 parts of plastic degradation masterbatch.
8. The heat shrinkable film according to claim 7, characterized in that: The opening agent is silicon dioxide; the white masterbatch is titanium dioxide; and the plastic degradation masterbatch is polylactic acid.
9. The heat shrinkable film according to claim 7, characterized in that: The heat shrinkable film is prepared by the following steps: through a three-layer co-extrusion biaxial stretching production process, the core film layer material and the surface film layer material are respectively fed, mixed, melt-plasticized and filtered and extruded, and then the heat shrinkable film is obtained after cast film, longitudinal stretching, transverse stretching, trimming and winding.
10. The heat shrinkable film according to claim 9, characterized in that: The filtration extrusion temperature of the core film layer is 250°C-270°C, and the filtration extrusion temperature of the surface film layer is 255°C-275°C; The preheating temperature in the longitudinal stretching is 95-105°C, the longitudinal stretching temperature is 85°C-95°C, the longitudinal stretching ratio is 1.0-3.0, the longitudinal stretching setting temperature is 75°C-90°C, and the longitudinal stretching setting time is 3-6 seconds; The preheating temperature in the transverse stretching is 105-125° C., the transverse stretching temperature is 85° C.-100° C., the transverse stretching ratio is 4-5.5 times, the transverse stretching setting temperature is 75° C.-90° C., and the transverse stretching setting time is 5-10 seconds.
Citation Information
Patent Citations
Water reducing agent, preparation method thereof and maleic acid mono alkyl ester polyether
CN101700964A
Method for preparing ester terminated allyl alcohol polyether
CN101701064A
Easily-recycled PETG (polyethylene terephthalate glycol) copolyester, heat-shrinkable film containing same and recycling method of heat-shrinkable film
CN118755065A
Biodegradable Heat-Shrinkable Production Method Thereof
US20090162630A1